A validated UHPLC–diode array detector method for the bioanalysis of atypical antipsychotics in whole blood, urine and cerebrospinal fluid following SPE. (December 2012) - Kovatsi, Leda; Redifis, Konstantinos; Mihailidou, Katia; Pavlidis, Pavlos; Samanidou, Victoria
Background: Risperidone, quetiapine, amisulpride and aripiprazole are atypical antipsychotics increasingly prescribed in Greece.Results: We have developed and validated a UHPLC–diode array detector method for the determination of these drugs in whole blood, urine and cerebrospinal fluid, following SPE. The separation was achieved within 7 min. Validation was performed in terms of linearity, selectivity, accuracy, precision and stability. Following validation, the method was applied to post-mortem blood, urine and cerebrospinal fluid samples.Conclusion: The method proved fast and simple for the determination of four atypical antipsychotic drugs in whole blood, urine and cerebrospinal fluid. To the best of our knowledge, this is the only available method for the simultaneous determination of these drugs in cerebrospinal fluid.